(3JaSjQ GdLdGdjfs - (3GdSjhWj GdNVjQj, CHh GdaVd, LdGd GdOjf, YHO GdQMef Hf CHj HcQ Hf eMeO, J (B911 (3gs ((3OeTb GdTGe (B( (3eOQSI GdHOQFjI (B)s)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg ehGajG dfYeg gPG eG GTJOJ Edjg MGLI GdQGZHjf aj JcedI JaSjQ GdbQBf GdPj Cdag LdGd GdOjf GdeMdj HSe Gddg GdQMef GdQMje Cde Gddg CYde HeQGOg aj Pdcs
(3BNQgG (B:s
(3GdVGdjf hge GdfUGQi hfcJI GdHOd EaGOI Gf GdegJOjf djShG jghOG hdG fUGQi hGddg Ld LdGdg hJbOSJ CSeGDg CYdes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B3 /301s
(3eYLe GdeDdajf (B2 / 82s
(3cTa GdXfhf (B1 / 445s
(3TPQGJ GdPgH (B7 / 303 (3, (B8 / 51s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs